Pharmacological potentials of Syzygium cumini: a review. (15th May 2013) - Srivastava, Shalini; Chandra, Deepak
Abstract In the last few years there has been an exponential growth in the field of herbal medicine, and these drugs are gaining popularity in both developing and developed countries because of their natural origin and lesser side effects. Syzygium cumini (syn. Eugenia jambolana, Syzygium jambolana, Eugenia cumini, Syzygium jambos), commonly known as jamun in India, is an evergreen tree distributed throughout the Indian subcontinent, Southeast Asia and East Africa. It is mainly utilised as a fruit producer and for its timber. Medicinally, the fruit is reported to have antidiabetic, antihyperlipidaemic, antioxidant, antiulcer, hepatoprotective, antiallergic, antiarthritic, antimicrobial, anti‐inflammatory, antifertility, antipyretic, antiplaque, radioprotective, neuropsychopharmacological, nephroprotective and antidiarrhoeal activities. Among these beneficial physiological effects, the antidiabetic property of S. cumini has the most promising nutraceutical value. The health‐beneficial effects of S. cumini are mainly attributed to various phytoconstituents such as tannins, alkaloids, steroids, flavonoids, terpenoids, fatty acids, phenols, minerals, carbohydrates and vitamins present in the fruit. This review paper presents an overview of experimental evidence for the pharmacological potential of S. cumini. © 2013 Society of Chemical Industry